Perancangan UI/UX Media Edukasi Warisan Budaya Indonesia Berbasis Kecerdasan Buatan untuk Pengalaman Belajar Personal - Vinkan Feriska Sahara; Agus Darmawan (MAN 4 Kota Pekanbaru, 2026)
The rapid development of digital technology has created new opportunities for delivering cultural information through interactive and accessible digital platforms. However, many cultural education applications still lack adequate attention to usability and user experience aspects. This study aims to design the User Interface (UI) and User Experience (UX) of an Artificial Intelligence (AI)–based Indonesian cultural heritage exploration application using the Design Thinking approach to provide an informative, engaging, and personalized learning experience. The research method follows the stages of empathize, define, ideate, prototype, and testing. The design process begins with user needs analysis, followed by the development of information architecture, user flow, wireframes, and a high-fidelity prototype. Usability evaluation was conducted using the System Usability Scale (SUS) involving 10 respondents. The usability testing results show an average SUS score of 76.5, which falls into the “Good” category and corresponds to grade B, indicating that the application demonstrates a satisfactory level of usability and effectiveness. Therefore, the proposed UI/UX design is considered effective in supporting interactive and personalized cultural exploration activities. This study is expected to serve as a reference for future development of digital cultural education applications that adopt a user-centered design approach integrated with AI technology.